Determinant Factors on Differences in Survival for Gastric Cancer Between the United States and Japan Using Nationwide Databases - Ito, Yuri; Miyashiro, Isao; Ishikawa, Takashi; Akazawa, Kohei; Fukui, Keisuke; Katai, Hitoshi; Nunobe, Souya; Oda, Ichiro; Isobe, Yoh; Tsujitani, Shunichi; Ono, Hiroyuki; Tanabe, Satoshi; et al. (Journal of epidemiology, 2021)
Although the incidence and mortality have decreased, gastric cancer (GC) is still a public health issue globally. An international study reported higher survival in Korea and Japan than other countries, including the United States. We examined the determinant factors of the high survival in Japan compared with the United States. We analysed data on 78,648 cases from the nationwide GC registration project, the Japanese Gastric Cancer Association (JGCA), from 2004-2007 and compared them with 16,722 cases from the Surveillance, Epidemiology, and End Results Program (SEER), a United States population-based cancer registry data from 2004-2010. We estimated 5-year relative survival and applied a multivariate excess hazard model to compare the two countries, considering the effect of number of lymph nodes (LNs) examined. Five-year relative survival in Japan was 81.0%, compared with 45.0% in the United States. After controlling for confounding factors, we still observed significantly higher survival in Japan. Among N2 patients, a higher number of LNs examined showed better survival in both countries. Among N3 patients, the relationship between number of LNs examined and differences in survival between the two countries disappeared. Although the wide differences in GC survival between Japan and United States can be largely explained by differences in the stage at diagnosis, the number of LNs examined may also help to explain the gaps between two countries, which is related to stage migration.